Osteomyelitis in adult patients on long-term parenteral nutrition: 2745 patient-years of experience in a national referral centre. Issue 5 (October 2016) - Allan, P.; Stevens, P.; Chadwick, P.; Teubner, A.; Abraham, A.; Carlson, G.; Lal, S.
Summary: Background & aims: Osteomyelitis (OM) is a rare complication of catheter related sepsis after central venous catheter (CVC) use. The prevalence, characteristics and diagnosis of OM in patients with intestinal failure (IF) receiving long term parenteral nutrition (PN) through CVCs have not previously been described. Methods: This was a retrospective study from a prospectively maintained database of patients referred to a National IF centre. Age, IF aetiology, past medical history, time on PN, OM site and organism(s) cultured were recorded. Patients were divided into 2 groups: OM occurring in the setting of acute (Type 2) IF (AIF) or chronic (Type 3) IF (CIF). Diagnosis of OM was made clinically and supported by radiological and/or microbial evidence. Results: 21 cases of OM occurred in 17 patients (7 male (41%)) between 1994 and 2014. 0 cases were observed between 1994 and 1999, 1 case between 2000 and 2004, 6 cases between 2005 and 2009 and 14 cases between 2010 and 2014. There were 11 cases in 7 patients with CIF managed at the IFU between 1994 and 2014; the latter yielded a period prevalence for OM of 0.9% when compared to the 794 HPN patients managed by the IFU over this period. There were 10 cases of OM in 10 patients with AIF; patients with AIF had spent less time on PN before developing OM, compared to patients with CIF; despite this, the rate of preceding CVC infections was higher in the AIF (5.6/1000 catheter days) than in the CIF (0.3/1000 catheter days) group, as a result of patients with AIF contracting CVC infections prior to specialist referral. Patients with AIF had more severe OM compared to those with CIF, according to the Cierny Mader classification. All patients received at least 6 weeks antimicrobial chemotherapy. 4/10 (40%) AIF cases and 2/11 (18%) CIF cases required surgical intervention. No patient died from OM or its treatment. Conclusion: OM is a rare complication of IF and its treatment, but is being diagnosed more frequently than before and should be noted as a potential focus of sepsis in patients with IF, because it may lead to considerable morbidity.